Online Mind-Map as Interface of Electronic Resource Integration and Sharing - 刘晓强 章田鑫 陶莉 任建军 李柏岩 杜明 (Shanghai jiao tong da xue xue bao, 2015)
The paper aims to research on online mind sharing. We developed a web application that provides map. With the online mind mapping tool, the electronic form of subject-oriented package, it is more flexibly than cooperation of the users are strengthened to some extent. map as interface of learning a interface to allow users to resource integration and create a knowledge mind learning resource will be discovered and shared in the the other E-Learning systems, and the interaction and